Microstructure, wear and corrosion characteristics of multiple-reinforced (SiC-B4C-Al2O3) Al matrix composites produced by liquid metal infiltration - Ozturk, Kubilay; Gecu, Ridvan; Karaaslan, Ahmet (ELSEVIER SCI LTD, 2021)
In this study, AA7075 aluminum matrix composites reinforced with the combination of SiC, Al2O3, and B4C particles were fabricated by the liquid metal infiltration method. The effects of the relative ratio of B4C and Al2O3 particles on the microstructural, wear, and corrosion features of the composite samples were analyzed using XRD, light metal microscopy, SEM, EDS, Brinell hardness, ball-on-disc type tribometer, and potentiodynamic polarization devices. It was determined that infiltration occurred more successfully, and homogenously distributed particles with reduced porosity were obtained as the amount of Al2O3 increased. Worn surface studies revealed that the specimens were predominantly worn by abrasion and adhesion. The increase in B4C/Al2O3 ratio caused a decrease in the hardness and wear strength, whereas it increased the corrosion resistance.
Keywords: Al matrix composite; SiC; B4C; Al2O3; Liquid metal infiltration; Wear; Corrosion; ALUMINUM-ALLOY; MECHANICAL CHARACTERIZATION; SILICON-CARBIDE; SIC PARTICLES; BORON-CARBIDE; BEHAVIOR; WETTABILITY; FABRICATION; ENHANCEMENT; SIZE; Materials Science